Legal Analysis of Regional Legislative Council Supervision of Regional Government Regarding Overlapping Mining Business Permits in North Maluku Province - Radina Hamza Hairun; Sultan Alwan; Nam Rumkel (Journal of Social Science, 2023)
This study aims to assess the authority of provincial governments related to mining business permits. Moreover, DPRD supervision of local governments related to overlapping of overlapping mining business permits in North Maluku Province. The research method used in this study is the type of research used in the research is normative legal research as a process to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced. The scientific logic that in normative legal research is built on scientific discipline and the ways in which normative legal science works, legal science whose object is law itself. The results of this study show that the authority of provincial governments related to mining business permits is explicitly regulated in the provisions of Article 14 paragraph (1) Law Number 23 of 2014 concerning Regional Government which reads "the implementation of government affairs in the fields of forestry, marine, as well as energy and mineral resources becomes a concurrent affair which is a division of authority between the central and provincial governments", The provisions of Article 14 paragraph (1) regulate mining business permits (IUP) which are no longer the authority of the regency government anymore, but become the authority of the provincial and central governments. The transfer of authority to issue mining business licenses (IUP), has a juridical impact on the provisions related to this matter will certainly change, but in its implementation the old provisions are used until there are new provisions that adapt to these rules.